2013
DOI: 10.1177/0149206313475815
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress and Employee Health

Abstract: Research examining the relationship between work stress and well-being has flourished over the past 20 years. At the same time, research on physiological stress processes has also advanced significantly. One of the major advances in this literature has been the emergence of the Allostatic Load model as a central organizing theory for understanding the physiology of stress. In this article, the Allostatic Load model is used as an organizing framework for reviewing the vast literature that has considered health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
345
2
26

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 643 publications
(383 citation statements)
references
References 142 publications
(197 reference statements)
10
345
2
26
Order By: Relevance
“…It poses a threat to workers' wellbeing by increasing mental and physical health risks (1,2). Work stress also contributes substantially to sickness absence (3).…”
mentioning
confidence: 99%
“…It poses a threat to workers' wellbeing by increasing mental and physical health risks (1,2). Work stress also contributes substantially to sickness absence (3).…”
mentioning
confidence: 99%
“…This proposition has to do with the notion that individuals cannot engage themselves in their work role if they do not have the personal capacity to become engaged. Stress literature confirms this fact as it suggests that when workers experience overload, they withdraw or disengage from work, perhaps in an effort to replenish their resources (Ganster & Schaubroeck, 1991;May et al, 2004). Further, research supports a positive relationship between psychological availability and work engagement (e.g., Kahn, 1990;May et al, 2004).…”
Section: Psychological Availabilitymentioning
confidence: 83%
“…Research has shown that role stress affects a number of organizational outcomes such as organizational commitment, citizenship behaviors, job satisfaction, and turnover intentions (e.g., Das, 2011 review;Fisher & Gitelson, 1983;Jackson & Schuler, 1985;Smith, 2010;Srivastave & Srivastava, 2009;Yousef, 2002). Role stress has also been associated with individual aspects of well-being such as burnout (Ashill & Rod, 2011), anxiety (Jackson & Schuler, 1985), depression (Beehr, 1998), and somatic complaints (Ganster & Schaubroeck, 1991;Sagiv & Schwartz, 2000).…”
Section: Value Congruence and Role Stressmentioning
confidence: 99%